2023
DOI: 10.1136/thorax-2022-219378
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal follow-up of postacute COVID-19 syndrome: DLCO, quality-of-life and MRI pulmonary gas-exchange abnormalities

Abstract: 129Xe MRI red blood cell to alveolar tissue plasma ratio (RBC:TP) abnormalities have been observed in ever-hospitalised and never-hospitalised people with postacute COVID-19 syndrome (PACS). But, it is not known if such abnormalities resolve when symptoms and quality-of-life scores improve. We evaluated 21 participants with PACS, 7±4 months (baseline) and 14±4 months (follow-up) postinfection. Significantly improved diffusing capacity of the lung for carbon monoxide (DLCO, Δ=14%pred;95%CI 7 to 21, p<0.001),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 10 publications
5
15
0
1
Order By: Relevance
“…It is reasonable to assume that SARS-CoV-2 induced destruction of alveolar cells and remodeling in extracellular matrix (Guizani et al, 2021) will result in structural acinar asymmetries, reflected by S acin . This alveolar epithelium injury is further supported by findings of reduced gas transfer ability in 129 Xe MRI studies in this patient group (Grist et al, 2022;Matheson et al, 2022Matheson et al, , 2023.…”
supporting
confidence: 69%
“…It is reasonable to assume that SARS-CoV-2 induced destruction of alveolar cells and remodeling in extracellular matrix (Guizani et al, 2021) will result in structural acinar asymmetries, reflected by S acin . This alveolar epithelium injury is further supported by findings of reduced gas transfer ability in 129 Xe MRI studies in this patient group (Grist et al, 2022;Matheson et al, 2022Matheson et al, , 2023.…”
supporting
confidence: 69%
“…Recently, the investigators reported on a small single-center group of 21 participants (seven female; mean age, 56 years) with PACS and persistently abnormal 129 Xe MRI red blood cell–to-tissue plasma ratio values 14 months after infection compared to baseline (7 months after COVID-19 infection). However, the participants also showed significantly normalized levels of percent predicted DL CO in the same observation period ( 8 ). In addition, Grist et al reported in a prospective study of 11 participants significant differences in mean red blood cell–to-tissue plasma ratio values between healthy volunteers and posthospitalized participants with post-COVID-19 condition and nonhospitalized participants with post-COVID-19 condition 5-9 months after COVID-19 infection, despite the presence of normal CT findings ( 9 ).…”
mentioning
confidence: 84%
“…So existiert zum einen eine umfangreiche Evidenz zu postinfektiösen Endorganschäden. Dabei konnten neben kardiopulmonalen Schädigungen [21,22,23,24] auch Beeinträchtigungen des zentralen Nervensystems festgestellt werden [25]. Bildgebende Studien wiesen strukturelle Schäden im olfaktorischen System nach einer überstandenen COVID-19-Erkrankung nach [26,27].…”
Section: Caveunclassified